Myopericarditis and Pericardial Effusion as the Initial Presentation of Systemic Lupus Erythematosus. (5th February 2017) - Bezwada, Prema; Quadri, Ahmed; Shaikh, Atif; Ayala-Rodriguez, Ceasar; Green, Stuart
Abstract : Myopericarditis with a pericardial effusion as the initial presenting feature of SLE is uncommon. We report an unusual case of myopericarditis and pericardial effusion with subsequent heart failure, as the initial manifestation of SLE. The timely recognition and early steroid administration are imperative in SLE-related myopericarditis with cardiomyopathy to prevent the mortality associated with this condition.